Practical evaluation of risk factors in patients with osteoporosis-induced thoracic and lumbar vertebral compression fractures requiring surgery - Hung Manh Do; Ha Thi-Ngoc Doan; Son Ngoc Dinh (Surgery in Practice and Science)
This descriptive longitudinal study aims to assess the risk factors for severe thoracic and lumbar vertebral compression fractures before and after surgery, contributing to preventive knowledge enhancement in communities and effective treatment management. The study involved 34 patients diagnosed with thoracic and lumbar vertebral compression fractures requiring surgery with bio-cement-augmented pedicle screws between June 2021 and June 2022. Postoperative complications, notably adjacent segment injury, were monitored, and patients received osteoporosis management post-surgery.The majority of patients were female (61.8 %), with an average age of 66.4 ± 9.2 years. Daily life accidents were the most common cause of injuries (88.2 %). Most patients underwent surgery more than 3 months after injury (58.8 %), with a notable percentage seeking examination and treatment post-injury. Osteoporosis prevalence was high among patients at the time of spinal injury, indicating a need for improved osteoporosis management strategies post-surgery. Various comorbidities were observed, with a portion of patients having pre-existing conditions like diabetes, hypertension, and kidney failure. Changes in bone mineral density correlated with age, highlighting the increased fracture risk seen in older individuals. Two patients required vertebral body reconstruction due to adjacent vertebra damage post-surgery. A significant proportion of patients received osteoporosis treatment after the surgical intervention.Patients with lumbar-thoracic osteoporosis fractures need a comprehensive assessment of clinical and paraclinical factors to select appropriate and effective treatment methods. Postoperatively, these patients also require osteoporosis management, regular monitoring, and evaluations to reduce postoperative complications, including the risk of adjacent segment injury and other vertebral compression fractures.